Exploration Of Physics Concepts In Tourism Sites For Basic Competency Of Grade 12 (IPF: Inovasi Pendidikan Fisika, 2021)
Abstract This study aims to determine the relationship between the rides in Jatim Park 3 with the basic competence (BC) of high school physics grade 12 and visitors' response to these rides. This study used a qualitative-quantitative design (Mixed Method) with a sequential exploratory mixed-method approach. The subjects used in this study were the visitors to Jawa Timur Park 3 who visited the infinity world rides and fun tech. The data from the relationship between BC and physics instruments were obtained from interviews with managers whose results were analyzed using qualitative descriptive and responses were obtained using a visitor response questionnaire, the results of which were analyzed using exploratory factor analysis. Based on the qualitative descriptive analysis, the results of the interviews conducted by Jatim Park 3 can be used as a means of study tours for grade 11 and 12. Based on the analysis of the exploratory factors in the visitor response questionnaire, it was found that the calculated KMO value is 0.845, and the p-value is 0.000 (<0.05), and it can be said that the data can be used. Most visitors did not understand the basic concepts of physics on the infinity world and fun tech rides and that visitors were enthusiastic about the study tour activities at Jatim Park 3. Keywords: Physics concept, tourism object, basic competence, visitor response Abstrak Penelitian ini bertujuan untuk mengetahui keterkaitan antara wahana di Jatim Park 3 dengan Kompetensi Dasar Fisika SMA kelas XII dan respons dari pengunjung terhadap wahana tersebut. Penelitian ini menggunakan desain kualitatif-kuantitatif (Mixed Method) dengan pendekatan metode campuran sekuensial eksploratori. Subjek yang digunakan dalam penelitian ini adalah para pengunjung Jawa Timur Park 3 yang mengunjungi wahana infinity world dan fun tech. Hasil data dari keterkaitan Kompetensi Dasar (KD) dan wahana fisika diperoleh dari wawancara terhadap pengelola yang hasilnya dianalisis menggunakan deskriptif kualitatif dan respon diperoleh menggunakan angket respon pengunjung yang hasilnya akan dianalisis menggunakan analisis eksplorasi faktor. Berdasarkan analisis deskriptif kualitatif pada hasil wawancara yang dilakukan Jatim Park 3 bisa digunakan sebagai sarana untuk study tour kelas XI dan XII. Berdasarkan analisis ekplorasi faktor pada angket respon pengunjung didapatkan nilai KMO yang terhitung sebesar 0,845 serta p-value sebesar 0,000 (< 0,05) dan dapat dikatakan bahwa data dapat digunakan. Sebagian besar pengunjung kurang paham dengana konsep dasar fisika pada wahana infinity world dan fun tech dan pengunjung antusias atas kegiatan study tour di Jatim Park 3. Kataikunci: Konsep fisika, obyek wisata, kompetensi dasar, respon pengunjung